2013
DOI: 10.1246/cl.130420
|View full text |Cite
|
Sign up to set email alerts
|

Solvate Ionic Liquid, [Li(triglyme)1][NTf2], as Electrolyte for Rechargeable Li–Air Battery: Discharge Depth and Reversibility

Abstract: This study reports a reversible oxygen reduction–oxygen evolution reaction (ORR–OER) that uses a solvate ionic liquid, [Li(triglyme)1][NTf2], as an electrolyte for a rechargeable Li–air (O2) battery. Significantly, it was found that the reversibility and capacity retention for ORR–OER in the solvate ionic liquid was greatly improved with a decrease in the ORR discharge depth; the discharge to 2.2 V vs. Li/Li+ gave much better reversibility than that to 2.0 V vs. Li/Li+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 18 publications
1
27
0
1
Order By: Relevance
“…The [Li(triglyme(G3)) 1 ][TFSI] solvate IL was used as the electrolyte of a rechargeable Li–air battery. This battery showed reversible ORR and OER characteristics, analogous to that of batteries with aprotic electrolytes . A [Li(TEGDME(G4)) 1 ][TFSI] solvate IL showed quasireversible ORR and OER behavior and high oxidative stability up to 4.5 V versus Li/Li + .…”
Section: Ionic‐liquid Electrolytesmentioning
confidence: 72%
“…The [Li(triglyme(G3)) 1 ][TFSI] solvate IL was used as the electrolyte of a rechargeable Li–air battery. This battery showed reversible ORR and OER characteristics, analogous to that of batteries with aprotic electrolytes . A [Li(TEGDME(G4)) 1 ][TFSI] solvate IL showed quasireversible ORR and OER behavior and high oxidative stability up to 4.5 V versus Li/Li + .…”
Section: Ionic‐liquid Electrolytesmentioning
confidence: 72%
“…In our previous study, 8 we applied a 1:1 mixture of Li salt and glyme for oxygen reduction/evolution. We have also recently shown that variation of the anion in such 1:1 solutions results in large differences in the amount of free glyme depending on the choice of Li salt.…”
Section: •¹mentioning
confidence: 99%
“…24 Many researchers have also reported the fundamental properties and possible applications of solvate ILs. [10][11][12][13]35,36 On the basis of the similarity of the chemical nature among congeners, an appropriate combination of glymes and other alkali-metal salts should potentially form solvate ILs. [25][26][27][28][29][30] Theoretical calculations of equimolar glyme-alkali metal salts have been performed to obtain stable solvate structures.…”
Section: Introductionmentioning
confidence: 99%